The K-transect on the western Greenland Ice Sheet: Surface energy balance (2003–2016). Issue 1 (1st January 2018) - Kuipers Munneke, P.; Smeets, C. J. P. P.; Reijmer, C. H.; Oerlemans, J.; van de Wal, R. S. W.; van den Broeke, M. R.
ABSTRACT: We present thirteen years (2003–2016) of surface energy balance calculations from automatic weather stations (AWS) along the K-transect in west Greenland. Although short in a climatological sense, these time series start to become long enough to provide valuable insight into the interannual variability and drivers of melt in this part of Greenland and into trends in certain components of the surface energy balance. For instance, the data clearly reveal that albedo variations explain most of the interannual melt variability at the higher stations in the accumulation zone. Sensible heat becomes a major heat source for melt in the lower ablation zone, while latent heat modulates annual melt by up to 20 W m −2 . Also, at two locations with the longest uninterrupted time series, we see a decreasing trend of incoming longwave radiation (−1.2 to −1.4 W m −2 y −1, p  < 0.10) concurrent with an increase in incoming shortwave radiation (+2.4 to +3.8 W m −2 y −1, p  < 0.10) during the observation period. This suggests that decreasing cloud cover plays a role in the increased availability of melt energy (+0.7 to +2.2 W m −2 y −1, not statistically significant at p  < 0.10). At the AWS situated around the equilibrium line altitude (ELA), the observed negative trend in albedo is strongest of all stations (−0.0087 y −1 ), as the ELA moves upward and bare ice becomes exposed. These insights are important for modeling the future response of the ice sheet to continued global warming, which is expected to be dominated by surface processes.